Music semiotics in a minor key: Deleuze and Guattari’s refrain and the musical topic. - Pihel, Karl Joosep (Sign Systems Studies, 2025)
Music semiotics spends considerable effort on establishing musical signification through relatively stable – if non-logocentric – concepts such as the musical ‘topic’. Like any signs, these concepts entail a stable generalized type which are instantiated in particular tokens. In contrast, Deleuze and Guattari praise music as an artform particularly suitable for deterritorialization, for becoming or events which do not proceed by the logic of the general opposed to the particular. This article probes the clash of these two perspectives on the contested battleground of musical meaning and proposes their mutual entwinement by comparing closely the concept of the ‘refrain’ from A Thousand Plateaus with the concept of musical ‘topic’ from semiotics, and the respective dynamics of these concepts. The clash results in a proposed re-orientation in the gaze of Deleuzean musicology to practices of signification as suggested by Iain Campbell and even to classical and traditional forms of music, but also to an internal distinction in music semiotics between mutually intertwined minor and major modes of practice, that is, practices oriented towards deterritorialization and territorialization, respectively. It is then demonstrated that a minor mode of interpretation is already present in musicologists’ writings on musical topics of the classical period.